Unpacking antigypsism and support for solidarity-based actions: Implications of social class, discrimination awareness, group efficacy and emotions - Cristina Carmona-López; Ana Urbiola; Marisol Navas; Soledad de Lemus (PLoS ONE, 2026)
Roma people, being the largest ethnic minority in Europe, continue to experience prejudice and structural discrimination. Moreover, there is low participation in Roma collective action and allies’ solidarity-based actions. This pre-registered experimental research examines on samples from non-Roma population in Spain how social class, discrimination awareness, and group efficacy predict prejudice towards Roma and non-Roma participation in solidarity-based actions as allies in addition to test the role of intergroup emotions on those effects. In Study 1 (N = 870) social class and discrimination awareness were manipulated. Results showed that individuals assigned to the low social class condition exhibited more prejudice towards Roma in terms of stereotypes, emotions and discriminatory behaviors. Moreover, discrimination awareness condition indirectly predicted more participation in pro-Roma solidarity-based actions through increased outrage about about the situation of Roma. Study 2 (N = 1,000) confirmed the effect of social class on prejudice. Further, it showed two different paths for predicting solidarity-based actions: discrimination awareness (high vs. low) predicted higher participation in solidarity-based actions indirectly via empathy towards Roma people and outrage towards about the situation of Roma, whereas group efficacy (high vs. low) predicted participation in solidarity-based actions through hope in relation to the situation of Roma and empathy towards Roma. This experimental research highlights the need to address the role of Roma social class as a crucial factor in understanding prejudice and confirms the discrimination (via outrage and empathy) and efficacy (via hope) routes for promoting solidarity-based actions participation to support Roma rights and promote social equity.